Answer:
279
Step-by-step explanation:
Answer:
b=2
Step-by-step explanation:
15b+10b=50
25b=50
b=2
Answer:
x-3
Step-by-step explanation:
f(x) = 3x – 2
g(x) = 2x + 1
(f – g)(x) = 3x-2 - ( 2x+1)
Distribute the minus sign
= 3x-2 -2x -1
= x -3
Answer:
-7 and 7
Step-by-step explanation:
Answer:
(s-t)(-1) = -1
(s+t)(-1) = -7
Step-by-step explanation:
Given the following set of functions
s(x)=2x-2
t(x)=3x
(s-t)(x) = s(t) - t(x)
(s-t)(x) = 2x - 2 - 3x
(s-t)(x) = -x -2
(s-t)(-1) = -(-1) - 2
(s-t)(-1) = 1-2
(s-t)(-1) = -1
(s+t)(x) = s(t) + t(x)
(s+t)(x) = 2x - 2 + 3x
(s+t)(x) = 5x -2
(s+t)(-1) = 5(-1) - 2
(s+t)(-1) = -5-2
(s+t)(-1) = -7